Reverse Migration Due to Long Lockdown in India- Is it Sustainable? - Dr. Sayantani Roy Choudhury; Ms. Suranjana Joarder (International Journal of Engineering and Management Research, 2020)
The ill fate of the migrants and their struggle to return home has been the highlights of media for many days now. The migrants do not want to come back to the cities in the future due to the traumatic experience faced. They are now eager to return to their land and sustain on the bare minimum that can be earned over there. As per the NSSO and Census data, there has been a significant migration to the urban cities from the rural areas; majority of these are of intrastate rural-urban migration nature. But the Census data does not consider the short- term circular migrants who account for a large percentage of the total migrant workforce. As per a survey conducted by NSSO in 2007-08, there had been 12.58 million short term migrant workers residing in rural India. They primarily shift to urban areas due to lack of return from agriculture and lack of opportunities in the rural areas. It has been observed that majority of the short term migrants possess low education level and belong to the low income strata with very meager ownership of assets. These migrants are primarily involved in hazardous low paying jobs in the urban cities without any social security. The ill treatment by the employers and lack of access to the facilities in their city of work is forcing them to return to their villages. In this study we have tried to analyse whether enough jobs can be created to absorb the reverse migrants.